2016
DOI: 10.18632/oncotarget.9387
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological investigation of glioblastomas resected under bevacizumab treatment

Abstract: To date, no clinical observations have been reported for histopathological changes in human gliomas under antiangiogenic treatment.We collected six glioblastomas resected under bevacizumab treatment. Histopathological investigation was performed by hematoxilyn-eosin staining and immunohistochemistry for CD34, VEGF, VEGFR1/2, HIF-1α, CA9, and nestin as compared to eleven control glioblastomas to assess the differences in histological features, microvessel density, expression of VEGF and its receptors, tumor oxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 29 publications
5
57
1
Order By: Relevance
“…Specifically, we hypothesize that bevacizumab induced vascular normalization results in improvement in tissue oxygenation. These findings are supported by histopathological evaluation of the effects of antiangiogenic therapies in patient-derived glioma specimens that demonstrate disappearance of microvascular proliferation, significant reduction of microvessel density, and reduction in endogenous molecular markers for tumor hypoxia suggesting improvement in tissue oxygenation [79]. These histological findings are supported by the observation in our cohort of a correlation between reduction in hypoxic volume and decreased rCBV occurring as a result of bevacizumab therapy.…”
Section: Resultssupporting
confidence: 85%
“…Specifically, we hypothesize that bevacizumab induced vascular normalization results in improvement in tissue oxygenation. These findings are supported by histopathological evaluation of the effects of antiangiogenic therapies in patient-derived glioma specimens that demonstrate disappearance of microvascular proliferation, significant reduction of microvessel density, and reduction in endogenous molecular markers for tumor hypoxia suggesting improvement in tissue oxygenation [79]. These histological findings are supported by the observation in our cohort of a correlation between reduction in hypoxic volume and decreased rCBV occurring as a result of bevacizumab therapy.…”
Section: Resultssupporting
confidence: 85%
“…41 Hypoxiainducible factor-1α was also able to activate the expression of PD-L1 by binding of HIF to a specific hypoxic response element in the promoter of PD-L1 in cancer cells. 42,43 We have previously reported that Bev improves tumor oxygenation in glioblastomas, 4 and that tumor hypoxia is regained in the post-Bev refractory tumors, to a similar or even higher level compared with the paired pre-Bev initial tumors. 5 In the present study, however, immunosuppressive cells and molecules in the tumors of refractory Bev group were still suppressed compared with the naïve Bev group despite recovery of hypoxia.…”
Section: Effect Of Continuous Vegf Blockade Vs Recovery Of Hypoxia mentioning
confidence: 92%
“…The present study used 47 glioblastoma tissues from 31 patients obtained at 3 different settings: 15 tumors resected following Bev therapy (under the Bev efficacy, defined as the "effective Bev group"), 20 tumors of initial glioblastoma (defined as the "naïve Bev group"), and 12 post-Bev recurrent tumors (defined as the "refractory Bev group") ( Table S1). The 15 tumors resected following Bev therapy (cases [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] were the tumors resected after 1-3 times of the preoperative Bev administration at a dose of 10 mg/kg for a safer surgical resection or as a consequence of the clinical course, and included 3 tumors enrolled in the phase II study of neoadjuvant Bev (UMIN000025579). Tumor resection was carried out 21-36 days after the last Bev treatment.…”
Section: Patients and Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…MDSCs are reported to differentiate into TAMs in the hypoxic microenvironment, which is regulated by STAT3 activity [60]. Since these immunosuppressive cells and immune checkpoint molecules show cross talk in the hypoxic TME, anti-VEGF/VEGFR therapy can induce tumor oxygenation [61], resulting in an immune-supportive TME.…”
Section: Cross Talk In the Tmementioning
confidence: 99%